Demand for international tourism in Africa: the role of financial development, trade openness, natural resources, and quality environment - Paul Adjei Kwakwa (Cogent Business & Management, 2024)
Studies have noted the potential benefits international tourism has to offer African economies. Consequently, research into the demand for international tourism especially for African countries has gained attention in recent years. What little is known about empirically is the effect that financial development, carbon dioxide emissions, trade openness and natural resources have on Africa's tourism. In this study international tourism is modelled as a function of financial development, carbon dioxide emissions, trade openness and natural resources while controlling for urbanization, exchange rate, economic growth and global financial crises effect. Data from seven African countries is explored for the 1995–2021 period. Regression analysis shows that in the long run, international tourism demand is positively enhanced by exchange rate, financial development, natural resources and trade openness. However, carbon dioxide emissions and global financial crises reduce demand for international tourism in the selected countries. The findings imply among others that commitment from governments in Africa to devote financial resources to support the attainment of low carbon economy will promote international tourism. Also, building a strong financial sector is recommended. Proper management of the abundant natural resources should be intensified.
Keywords: 650; tourism; financial development; carbon dioxide emission; renewable energy